Spanish phrases for dummies - Wald, Susana (Wiley, 2004)
Traveling to Latin America or Spain but don’t know Spanish? Taking Spanish at school but need to kick up your conversation skills? Don’t worry! This handy little phrasebook will have you speaking Spanish in no time. Discover how to: Get directions, shop, and eat out; Talk numbers, dates, time, and money; Chat about family and work; Discuss sports and the weather; Deal with problems and emergencies.